EDUCATION MARKETING MIX STRATEGY IN INCREASING STUDENT INTEREST - Nifasri; Alkausar, Anisa; Syahdiah, Ainul (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This research examines the educational marketing strategy implemented by MTsN 36 Jakarta in an effort to increase the interest of new students. Utilizing observation and interviews, this study explores various aspects of the marketing strategy applied, including educational promotion, academic and extracurricular programs, student achievements, education costs, facilities, and educational services. The research findings indicate that MTsN 36 Jakarta implements a comprehensive promotion strategy through the utilization of digital media and direct promotional activities. The school offers diverse and high-quality academic and extracurricular programs, supported by excellent student achievements. A key advantage of the school lies in its free education costs for students, while still providing adequate facilities and services. The implemented marketing strategy has proven effective in attracting prospective new students by offering optimal value and benefits for students and parents in obtaining quality education. This research also analyzes MTsN 36 Jakarta's strategy within the context of the 7P service marketing mix (Product, Price, Place, Promotion, People, Process, Physical Evidence), demonstrating how these elements synergistically support the school's marketing objectives.